Effect of Nd:YAG Laser Irradiation on the Number of Open Dentinal Tubules and Their Diameter with and without Smear of Graphite: An in Vitro Study - Maleki-pour, Mohammad Reza; Birang, Reza; Khoshayand, Maryam; Naghsh, Narges (Journal of Lasers in Medical Sciences, 2014)
Introduction: Dentin hypersensitivity (DH) is characterized by tooth pain arising from exposure of dental roots. In this study the efficiency of neodymium yttrium-aluminum-garnet (Nd:YAG) laser in association with graphite on dentinal surface changes as the alternative to the treatment of DH was evaluated. Methods: Sixteen noncarious human third molars were collected and sectioned into 5 parts from cementoenamel junction (CEJ) to the furcation area. The prepared samples were randomly assigned into five groups (Gs) of each 16: Control (G1), treated by Nd:YAG laser at 0.5 W (G2), irradiation of Nd:YAG with a 0.25 W output power(G3), smeared with graphite and then using Nd:YAG laser at output powers of 0.5 W (G4) and 0.25 W (G5). For all groups the parameters were 15 Hz, 60 s, at two stages and with a right angle irradiation. The number and diameter of dentinal tubules (DT) were compared and analyzed by SPSS software, One way ANOVA and Post hoc LSD tests. Results: The number of open dentinal tubules varied significantly between all groups except among G1 with G3 and G2 with G5. Multiple comparison tests also exhibited significant differences regarding the diameter of tubules between the groups two by two except among G2 with G5. Conclusion: Nd:YAG laser used at 0.25 W and 0.5 W with application of graphite smear was able to reduce the number and diameter of dentinal tubules.